2020
DOI: 10.1101/2020.04.02.021972
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pod indehiscence in common bean is associated to the fine regulation ofPvMYB26and a non-functional abscission layer

Abstract: Short title:The pod-shattering syndrome in common bean 32 33 One-sentence summary: A non-functional abscission layer determines the loss of pod 34 shattering; mapping data, and parallel gene expression and histological analysis support 35 PvMYB26 as the candidate gene for pod indehiscence.36 37The author responsible for distribution of materials integral to the findings presented in this 38 article in accordance with the policy described in the Instructions for Authors 39 (www.plantcell.org) is: Roberto Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 45 publications
1
14
1
Order By: Relevance
“…This observation is similar to that described in Brassica species, where indehiscent species show a more lignified endocarp than dehiscent ones 54 . By contrast, our findings are opposed to those reported from histological studies in common bean and soybean, where pod valves of the wild dehiscent lines showed a strong lignified wall fiber layer contrasting with a complete absence of lignin deposition in the indehiscent lines 21 , 26 , 34 , 55 , 56 , 58 .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This observation is similar to that described in Brassica species, where indehiscent species show a more lignified endocarp than dehiscent ones 54 . By contrast, our findings are opposed to those reported from histological studies in common bean and soybean, where pod valves of the wild dehiscent lines showed a strong lignified wall fiber layer contrasting with a complete absence of lignin deposition in the indehiscent lines 21 , 26 , 34 , 55 , 56 , 58 .…”
Section: Discussioncontrasting
confidence: 99%
“…Histological characterization of the faba bean pod sutures in mature pods revealed anatomical structures analogous to those described in other legumes such as soybean, common bean, pea or common vetch 22 , 26 , 30 , 36 , 55 , 56 . Pod dehiscence arises from fissures that initiate in the ventral sutures, as recently observed in chickpea by Aguilar-Benitez 28 .…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…On the other hand, MYB26 is expressed in seed pods in many legume species according to the expression database [ Vig GS, the Phaseolus vulgaris Gene Expression Atlas ( Pv GEA) 8 and Soybean eFP Browser 9 ]. In addition, Di Vittori et al (2020) has recently revealed in common bean that reduced expression of MYB26 is a key for non-shattering genotypes. Thus, in legumes, MYB26 plays a crucial role in the development of pod sclerenchyma and has been a common target of human selection among the three independently domesticated legumes, azuki bean, cowpea, and common bean.…”
Section: Discussionmentioning
confidence: 99%
“…A recently discovered QTL on Pv05, in immediate vicinity of PvMYB26, is associated with a loss of dehiscence in the Andean gene pool (Rau et al 2019;Parker et al 2020;Di Vittori et al 2020). This locus was mapped in detail in a biparental recombinant inbred population (Rau et al 2019), which also found signiicant QTLs on Pv04 and Pv09 in the same population.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 93%